Revealing the Impact of Oxygen Dissolved in Electrolytes on Aqueous Zinc-Ion Batteries - Su, Lijun; Liu, Lingyang; Liu, Bao; Meng, Jianing; Yan, Xingbin (iScience, 2020)
Aqueous zinc-ion batteries (ZIBs) are promising low-cost and high-safety energy storage devices. However, their capacity decay especially at the initial cyclic stage is a serious issue. Herein, we reveal that the dissolved oxygen in aqueous electrolyte has significant impact on the electrochemistry of Zn anode and ZIBs. After removing oxygen, the symmetrical set-up of Zn/Zn is capable of reversible plating/stripping with a 20-fold lifetime enhancement compared with that in oxygen enrichment condition. Taking aqueous Zn-MnO2 battery as an example, although the presence of oxygen can contribute an extra capacity over 20% at the initial cycles due to the electrocatalytic activity of MnO2 with oxygen, the corrosion of Zn anode can be eliminated in the oxygen-free circumstance and thus offering a better reversible energy storage system. The impact of the dissolved oxygen on the cycling stability also exists in other ZIBs using vanadium-based compounds, Birnessite and Prussian blue analog cathodes. [Display omitted] •Dissolved oxygen in electrolyte has significant impact on Zn anode and ZIBs•The dissolved oxygen caused the thermodynamically instability of Zn•Oxygen dissolved in electrolyte accelerates the corrosion on Zn•The ZIBs present better cycling stability after removing oxygen Electrochemical Energy Storage; Energy Storage; Materials Characterization